Analysis of Driver Design for 3.3 kV IGBT Module - 郑姿清 (Kongzhi Yu Xinxi Jishu)
3.3 kV IGBT modules produced by infineon have been accepted by many customers. The driver board for 3.3 kV IGBT modules has some differences from 1.2 kV and 1.7 kV modules′. The design details of driver circuit are analyzed to promote application of the 3.3 kV IGBT modules.